THE ASPECTS OF QUALITY MANAGEMENT IN CONTINIOUS PROFESSIONAL TRAINING OF TEACHERS - Viorica ANDRIȚCHI (Acta et Commentationes, Sciences of Education, 2019)
This article addresses the problem of the quality for professional forming of teachers. As aresult of the comparative analysis and experimental studies, it was deduced the criteria of the quality forprofessional forming; thus there are highlighted the principles for confirming the quality training ofteachers and also it was proposed a series of actions for implementing appropriate the system ofmanagement quality in institutions of professional forming.